THE EFFECT OF SERVICE QUALITY, PRICE, AND FACILITIES ON CUSTOMER SATISFACTION OF BOAT CHARTERING AT PT. MITRA TSUNAMI LAUT - Lulu Adelia; Yahya Tanjung (CV. Radja Publika, 2026)
Customer satisfaction is very important for companies engaged in air transportation services in the increasingly tight business competition conditions as it is today. One of the strategic advantages for companies regarding the importance of maintaining customer satisfaction is the reward of long-term and cumulative satisfaction. This type of research uses associative research with quantitative methods. Data sources consist of primary data and secondary data. The location of the research was carried out by PT. Mitra Tsunami Marine, located at Jl. TM Pahlawan Lor. Pemancar No. 100 Belawan- North Sumatra -20411. The time of this research was conducted from March 2025 to January 2026. The population in this study were customers of PT. Mitra Tsunami Marine whose number could not be known with certainty. Due to cost, distance and time limitations, the researcher directly determined the number of samples in this study was 42 respondents. The data collection technique in this study used a research questionnaire, with linear regression analysis and analysis tools using SPSS version 26. The results of this study Service quality does not have a partial positive and significant effect on customer satisfaction at PT. Mitra Tsunami Marine. Price does not have a partial positive and significant effect on customer satisfaction at PT. Mitra Tsunami Marine. Facilities have a partial positive and significant effect on customer satisfaction at PT. Mitra Tsunami Marine. Service quality, price, and facilities simultaneously have a positive and significant effect on customer satisfaction at PT. Mitra Tsunami Marine.